The supply chain for academic books: Why is it so complex and how might we drive change?. Issue 4 (4th September 2017) - Jubb, Michael; Fisher, Richard
Abstract : Key points The supply chain for monographs and related types of books is much more complex than that for journals. Sales per title are falling, while the efforts devoted to marketing individual titles have diminished too. Readers have a strong preference for physical print rather than e‐books, while libraries' preference in purchasing is the other way round. Publishers, intermediaries, and libraries all face additional costs and complexity because they must continue to deal with both print and e‐books. Current inefficiencies in the supply chain act as a restraint on discoverability, demand, and access to academic books.